Preoperative Embolization of Cerebral Arteriovenous Malformations with Onyx - Hauck, E.F.; Welch, B.G.; White, J.A.; Purdy, P.D.; Pride, L.G.; Samson, D. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Preoperative embolization facilitates the surgical management of complex cerebral arteriovenous malformations (cAVMs). This analysis aims to investigate the risks for preoperative cAVM embolization with Onyx.MATERIALS AND METHODS: We retrospectively analyzed clinical data of all patients who underwent embolization with Onyx as a preoperative treatment of cAVMs at our institution since 2005 (US Food and Drug Administration [FDA] approval). Patients with arteriovenous fistulas were excluded. A total of 107 patients were treated for cAVMs during the study period. Of those patients, 41 underwent cAVM embolizations with Onyx in 82 procedures.RESULTS: After the embolization, the cAVM diameter was reduced from 3.71 ± 1.55 cm to 3.06 ± 1.89 cm (P < .05). Median volume reduction was 75%. Complete occlusion with embolization alone was achieved in 4 (10%) cAVMs. The recurrence rate for completely occluded cAVMs was 50% (2 patients). A total of 71% of the 41 patients treated with Onyx underwent surgery, and 15% underwent radiosurgery. There were 9% who have not yet received definitive treatment of their residual cAVMs. A new permanent neurologic deficit occurred in 5 patients (6.1% per procedure or 12.2% per patient).CONCLUSIONS: A considerable risk for a permanent neurologic deficit remains for cAVM embolization with Onyx. The risk has to be carefully weighted against the benefit of volume reduction in the treatment of cAVMs.